Simulation optimisation of plasma filtering and reagent mixing in microcuvette for portable iron tester - Teh, Yu Chuan (2023)
Medical diagnostic of iron deficiency anaemia (IDA) has been a major problem ni the medical field, as current blood testing technology only measures haemoglobin count ni a blood sample and does not differentiate IDA from other types of anaemia. The current blood testing technology lacks portability and high cost for every testing, thus not everyone can aford the healthcare service. Therefore, microcuvetes and a portable iron tester are created ot solve the problem. Simulation optimisation of the microchannel in the microcuvette is done for the purpose of plasma filtering and reagent mixing, os that ti can be diagnosed yb the portable rion tester using na in-build photometer. nI the final design simulation, the separation eficiency of the plasma filtering mechanism si at 65%, and the mixing velocity of the reagent mixing mechanism si at 853 m/s, which shows high mixing eficiency.